The Value of Strain Elastography in Predicting Autoimmune Thyroiditis - Cristina Mihaela Cepeha (Diagnostics, 2020)
Chronic autoimmune thyroiditis (CAT) defines a diffuse intrathyroidal lymphocytic infiltration associating a destructive process of the thyroid follicles, most commonly in evolution developing hypothyroidism. Typical ultrasound changes may suggest the presence of the disease. This study aims to evaluate the performance of strain elastography in detecting autoimmune thyroiditis as an additional tool to the conventional ultrasound examination. A total of 250 patients were enrolled in the study; 180 had biochemical confirmation of CAT, the other 70 healthy subjects represented the control group. All patients were examined clinically and by means of conventional thyroid ultrasound (US) and real-time elastography using a Hitachi Preirus machine (5–15 MHz linear probe). Five valid measurements for the parenchyma/muscle strain ratios (SR) were taken for each subject, considering the mean value for analysis. A mean SR value above 1.64 was found to predict the presence of CAT with sensitivity (Sen) 69%, specificity p92%, positive predictive value (PPV) 95.4%, negative predictive value (NPV) 54% and area under receiver operating characteristic (AUROC) 0.87. Moreover, when comparing the mean values for SR, significantly higher values were found in CAT patients compared with the controls (2.81 ± 2.11 vs. 1.03 ± 0.51; p < 0.0001). Of the 180 CAT subjects, 92 were on thyroid hormone replacement therapy; significantly higher values were detected for patients under therapy compared with asymptomatic cases (3.45 ± 2.53 vs. 2.15 ± 1.27, p < 0.0001). A cut-off value of 2.94 was established for identifying CAT patients who needed hormonal treatment (Sen 52.3%, Sp 83.7%, PPV 75.4%, NPV 64.7% and AUROC 0.66). No correlation was found between stiffness and antibody titers nor for functional status. Elastography does add valuable information to the US evaluation of cases with autoimmune thyroiditis.